Forensic estimation of time of death: A mathematical model - Kwach, Boniface O.; Ongati, Naftali O.; Nyakinda, J. O; Nyang’inja, Rachael (International Journal of Management, IT and Engineering, 2013)
In this paper we establish the exact time of death of a murdered person. This leads to an ordinary differential equation whose solution has been analyzed to provide the approximate time of death. Forensic expert will try to estimate this time from body’s current temperature and calculating how long it would have taken to lose heat to reach this point. This provides an accurate approach to establish the approximate time when crime is committed
Keywords: Forensic Science; Postmortem Interval; Forensic Entomology